Verify Mean Value Theorem, if $f(x)=x^{3}-5 x^{2}-3 x$ in the interval $[a, b],$ where $a=1$ and $b=3 .$ Find all $c \in(1,3)$ for which $f^{\prime}(c)=0$
The given function $f$ is $f(x)=x^{2}-5 x^{2}-3 x$
$f,$ being a polynomial function, is continuous in $[1,3],$ and is differentiable in $(1,3)$
Whose derivative is $3 x^{2}-10 x-3$
$f(1)=1^{2}-5 \times 1^{2}-3 \times 1=-7, f(3)=3^{3}-3 \times 3=27$
$\therefore \frac{f(b)-f(a)}{b-a}=\frac{f(3)-f(1)}{3-1}=\frac{-27-(-7)}{3-1}=-10$
Mean Value Theorem states that there exist a point $c \in(1,3)$ such that $f^{\prime}(c)=-10$
$f^{\prime}(c)=-10$
$\Rightarrow 3 c^{2}-10 c-3=10$
$\Rightarrow 3 c^{2}-10 c+7=0$
$\Rightarrow 3 c^{2}-3 c-7 c+7=0$
$\Rightarrow 3 c(c-1)-7(c-1)=0$
$\Rightarrow(c-1)(3 c-7)=0$
$\Rightarrow c=1, \frac{7}{3}$ where $c=\frac{7}{3} \in(1,3)$
Hence, Mean Value Theorem is verified for the given function and $c=\frac{7}{3} \in(1,3)$ is the only point for which $f^{\prime}(c)=0$
If $f$ and $g$ are differentiable functions in $[0, 1]$ satisfying $f\left( 0 \right) = 2 = g\left( 1 \right)\;,\;\;g\left( 0 \right) = 0,$ and $f\left( 1 \right) = 6,$ then for some $c \in \left] {0,1} \right[$ . .
Number of solution of the equation $ 3tanx + x^3 = 2 $ in $ \left( {0,\frac{\pi }{4}} \right)$ is
Let $f :[2,4] \rightarrow R$ be a differentiable function such that $\left(x \log _e x\right) f^{\prime}(x)+\left(\log _e x\right) f(x)+f(x) \geq 1$, $x \in[2,4]$ with $f(2)=\frac{1}{2}$ and $f(4)=\frac{1}{4}$.
Consider the following two statements:
$(A): f(x) \leq 1$, for all $x \in[2,4]$
$(B)$ : $f(x) \geq \frac{1}{8}$, for all $x \in[2,4]$
Then,
If $f(x) = \cos x,0 \le x \le {\pi \over 2}$, then the real number $ ‘c’ $ of the mean value theorem is
Let $f$ and $g$ be real valued functions defined on interval $(-1,1)$ such that $g^{\prime \prime}(x)$ is continuous, $g(0) \neq 0, g^{\prime}(0)=0, g^{\prime \prime}(0) \neq$ 0 , and $f(x)=g(x) \sin x$.
$STATEMENT$ $-1: \lim _{x \rightarrow 0}[g(x) \cot x-g(0) \operatorname{cosec} x]=f^{\prime \prime}(0)$.and
$STATEMENT$ $-2: f^{\prime}(0)=g(0)$.